2006
DOI: 10.1101/gad.1478706
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 is dispensable for normal pancreas development yet critical in progression and tumor biology of pancreas cancer

Abstract: SMAD4 is inactivated in the majority of pancreatic ductal adenocarcinomas (PDAC) with concurrent mutational inactivation of the INK4A/ARF tumor suppressor locus and activation of the KRAS oncogene. Here, using genetically engineered mice, we determined the impact of SMAD4 deficiency on the development of the pancreas and on the initiation and/or progression of PDAC-alone or in combination with PDAC-relevant mutations. Selective SMAD4 deletion in the pancreatic epithelium had no discernable impact on pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
553
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 599 publications
(589 citation statements)
references
References 53 publications
(68 reference statements)
34
553
0
2
Order By: Relevance
“…We confirmed that TGF-β induced Bgn expression in 4A cells and not in W1 cells (Supplementary Figure S4a), suggesting that Bgn expression, after TGF-β treatment, is dependent on TAp73. The tumor-suppressor role of TGF-β in pancreatic cancer is mainly mediated by SMAD4, a transcription factor, inactivated in half of invasive PDA 41 and known to induce Bgn expression after TGF-β treatment. 42 Interestingly in TAp73-deficient cells, we observed a decrease in SMAD4 (Figure 6a) consistent with the presence of p53-responsive elements in all promoters of Smad genes.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that TGF-β induced Bgn expression in 4A cells and not in W1 cells (Supplementary Figure S4a), suggesting that Bgn expression, after TGF-β treatment, is dependent on TAp73. The tumor-suppressor role of TGF-β in pancreatic cancer is mainly mediated by SMAD4, a transcription factor, inactivated in half of invasive PDA 41 and known to induce Bgn expression after TGF-β treatment. 42 Interestingly in TAp73-deficient cells, we observed a decrease in SMAD4 (Figure 6a) consistent with the presence of p53-responsive elements in all promoters of Smad genes.…”
Section: Resultsmentioning
confidence: 99%
“…2D), suggesting that miR-483-3p can regulate DPC4/Smad4-regulated signaling pathways. It is known that DPC4/Smad4 is involved in TGF-b-induced epithelial-mesenchymal transition (EMT) [32], and that pancreatic cancers with wild type DPC4/Smad4 show frequent EMT [33]. To test the possibility that miR-483-3p could regulate the DPC4/ Smad4-mediated EMT process, we transfected PANC1 cells with miR-483-3p mimics or scramble oligos and simultaneously treated them with TGF-b.…”
Section: Dpc4/smad4 Is a Direct Target Of Mirna-483-3pmentioning
confidence: 99%
“…Xenograft tumor tissue processing and immunohistochemical (IHC) staining were performed as previously described (24). The IHC analysis was performed as previously described using anti-LKB1 (Cell Signaling Technology), anti-c-Myc (Santa Cruz Biotechnology), anti-survivin (Santa Cruz Biotechnology), and anti-COX2 (Santa Cruz Biotechnology) antibodies.…”
Section: Tumor Necropsy Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…MTT (Amresco) was added to 25 mL of cell suspension in 500 mL of medium and incubated for 2 hours as previously described (24).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation